2023
DOI: 10.1002/brb3.2868
|View full text |Cite
|
Sign up to set email alerts
|

The core of maintaining neuropathic pain: Crosstalk between glial cells and neurons (neural cell crosstalk at spinal cord)

Abstract: Background Neuropathic pain (NP) caused by the injury or dysfunction of the nervous system is a chronic pain state accompanied by hyperalgesia, and the available clinical treatment is relatively scarce. Hyperalgesia mediated by pro‐inflammatory factors and chemokines plays an important role in the occurrence and maintenance of NP. Data treatment Therefore, we conducted a systematic literature review of experimental NP (PubMed Medline), in order to find the mechanism of inducing central sensitization and explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 195 publications
1
5
0
Order By: Relevance
“…Microglia and astrocyte activation lead to overregulation of chemokines and increased signalling between neurons and glial cells. Moreover, neurons can maintain glial cell activation through chemokines and related pathways [67]. Among the different mediators implicated in these interactions, a role is played by cytokines, like IL-1beta [68][69][70], whose expression in the present study was found to be increased in trigeminal areas of operated animals, along with other pro-inflammatory molecules.…”
Section: Discussionsupporting
confidence: 46%
“…Microglia and astrocyte activation lead to overregulation of chemokines and increased signalling between neurons and glial cells. Moreover, neurons can maintain glial cell activation through chemokines and related pathways [67]. Among the different mediators implicated in these interactions, a role is played by cytokines, like IL-1beta [68][69][70], whose expression in the present study was found to be increased in trigeminal areas of operated animals, along with other pro-inflammatory molecules.…”
Section: Discussionsupporting
confidence: 46%
“…Based on the strong effect of SAFit2 on pain-mediating chemokines in the lumbar DRGs and spinal cord, we investigated the effect of SAFit2 regarding spinal gliosis, since activated astrocytes and microglia are the predominant source of cytokines and chemokines in the spinal cord [ 30 , 31 ]. To assess this, we performed immunohistochemical stainings of dorsal horn samples to assess the activation of astrocytes and the number of microglia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CNS involvement can account for bilateral neuropathy symptoms, which may be due to DRGn hyperactivity-induced hyperexcitability of wide dynamic range neurons and activation of commissural neurons of the spinal cord ( 66 ), or, also supposedly, due to systemic neuroinflammation-mediated mechanisms ( 42 , 66 ). Extraterritorial hypersensitivity may be shaped by neuron crosstalk not only in the CNS ( 112 , 113 ) but also in the DRG ( 83 ). Notably, allodynia involves functional interplay between nociceptive and non-nociceptive pathways ( 2 , 16 ).…”
Section: Pre-hypothetical Reasoning: Ectopic Nociceptive Sensitizatio...mentioning
confidence: 99%